The efficient market hypothesis is usually addressed indirectly: what happens if a direct approach is used instead? - Samsa, Greg (Archives of Business Research, 2021)
A vast literature on putative market inefficiencies compares the results of an investment strategy which takes advantage of the putative inefficiency against a null hypothesis generated by the efficient market hypothesis (EMH). Even if negative, such studies do not provide direct evidence in favor of the EMH. To directly assess a key component of the EMH, namely that stock returns lack memory, we created 30-year portfolios by sampling annual market returns from 1926-2019 with replacement, and then compared the results with the historical record of actual 30-year returns. Although centered on the correct amount, the EMH-based 30-year returns were notably more variable than the historical 30-year returns. One possible explanation is that market returns regress toward their mean in the long term. This demonstrates that while the EMH should be taken seriously, it need not always be taken literally.